Metal oxide nanostructures and nanocomposites for selective catalytic reduction of nox: A review - Irfan, M.F.; Qurashi, A.; Alam, M.W. (Springer Heidelberg, 2010)
Nitrogen oxides (NO) are the major air pollutants that have to be removed before emitting flue gas into the atmosphere. These pollutants in the atmosphere directly affect not only human health, but also the ecosystem. Air pollution is no longer a local problem limited only to a nation but a global problem. As a result, environmental taxes and trade restrictions have been imposed on the pollutant sources. Therefore, removal of these contaminants in compliance with the environmental emission standards is necessary and various wet and dry processes have been proposed so far. The control technologies of NOx from flue gas of satisfactory sources have been commercialized by various methods such as selective catalytic reduction (SCR) and selective non-catalytic reduction (SNCR). These technologies, especially SCR, are very attractive for the removal of NOx because of their low cost and high efficiency. The SNCR process results in low DeNO(x) conversion and requires a high temperature compared to SCR, but the SCR process still needs a high temperature to increase the rate of reaction. In order to achieve highly selective catalysts for N-2 at low temperature, various types of catalysts have been tested, and researchers are developing new catalysts for this process. Among the numerous catalysts used, vanadium oxide-based catalysts proved to be the commercial catalyst. Hence, most of the SCR study focuses on this catalyst. However, recently, other transition metals oxides and their composites have been investigated. This paper also briefly reviews the role of the formation of the nanostructure and nanocomposites of these metal oxide catalysts used for the removal of NOx.